Y se crearon las redes académicas de alta velocidad... y vieron que era bueno. (2021)
Mass media developing has allowed generating a new dynamic when it comes to information collaboration and interchange. Not only for commercial organizations but also for academic ones. That is why since ages ago, Universities and investigation centers have discovered huge working potential surrounding computer webs, which makes an easier collaborative access to those resources that would not be possible in other circumstances at not any reason. This way, the present article presents the evolution, research and target of the High Velocity Academics Networks, expecting to generate a space of analysis and discussion about their opportunities and potentials.